Classification Techniques for Medical Image Analysis and Computer Aided Diagnosis - Dey, Nilanjan (Academic Press, 2019)
Classification Techniques for Medical Image Analysis and Computer Aided Diagnosis covers the most current advances on how to apply classification techniques to a wide variety of clinical applications that are appropriate for researchers and biomedical engineers in the areas of machine learning, deep learning, data analysis, data management and computer-aided diagnosis (CAD) systems design. The book covers several complex image classification problems using pattern recognition methods, including Artificial Neural Networks (ANN), Support Vector Machines (SVM), Bayesian Networks (BN) and deep learning. Further, numerous data mining techniques are discussed, as they have proven to be good classifiers for medical images.
Print version record
Keywords: Diagnostic imaging -- Digital techniques; Imagerie pour le diagnostic; Techniques numériques; Diagnostic imaging; Digital techniques